POD nanozyme optimized by charge separation engineering for light/pH activated bacteria catalytic/photodynamic therapy - Cao, Changyu (2023)
The current feasibility of nanocatalysts in clinical anti-infection therapy, especially for drug-resistant bacteria infection is extremely restrained because of the insufficient reactive oxygen generation. Herein, a novel Ag/Bi2MoO6 (Ag/BMO) nanozyme optimized by charge separation engineering with photoactivated sustainable peroxidase-mimicking activities and NIR-II photodynamic performance was synthesized by solvothermal reaction and photoreduction. The Ag/BMO nanozyme held satisfactory bactericidal performance against methicillin-resistant Staphylococcus aureus (MRSA) (~99.9%). The excellent antibacterial performance of Ag/BMO NPs was ascribed to the corporation of peroxidase-like activity, NIR-II photodynamic behavior, and acidity-enhanced release of Ag+. As revealed by theoretical calculations, the introduction of Ag to BMO made it easier to separate photo-triggered electron-hole pairs for ROS production. And the conduction and valence band potentials of Ag/BMO NPs were favorable for the reduction of O2 to ·O2-. Under 1064 nm laser irradiation, the electron transfer to BMO was beneficial to the reversible change of Mo5+/Mo6+, further improving the peroxidase-like catalytic activity and NIR-II photodynamic performance based on the Russell mechanism. In vivo, the Ag/BMO NPs exhibited promising therapeutic effects towards MRSA-infected wounds. This study enriches the nanozyme research and proves that nanozymes can be rationally optimized by charge separation engineering strategy.